PERBANYAKAN INOKULUM FUNGI MIKORIZA ARBUSKULAR (FMA) SECARA SEDERHANA - Herryawan K.M (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
The availability of supplying a high quality forage and fodder throughout years is essential to increase ruminant livestock production. However, special land availability for planting forage is very limited, if any, there is only marginal land. Legume introduction is the only way to improve marginal lands productivity. A high feed quality could be provided by planting mix grasses and legumes, especially when equipped with sustainable fertilizing soil technology as the AMF biological fertilizer. In order to obtain a low price experiments and easy AMF biological fertilizer, propagation of AMF inoculum biological fertilizer could be carried out by using mycofer starter, consists of: Gigaspora margarita, Glomusmanihotis (Indo-1), Glomusetunicatum and Acaulosporatuberculata (Indo-2). The media used were soil exploration taken from field and polybag multiplication with a host bearing of corn crop. And then, results of AMF inoculum multiplication were named as Ifapet. The statistical test showed that significant differences number of spores found in pre and post treatments. Furthermore, t-tests showed that AMF inoculum applied significantly affected to the number of spores. It can be concluded that Ifapet AMF inoculum produced by using simple method to improve crop productivity and increased marginal soil fertility.